Mirror, Mirror on the Wall, Who is the Most Autonomous of Them All? - Ebru Sınar Okutucu (Studies in Self-Access Learning Journal, 2021)
Learner Autonomy is a key element in the field of education, and the number of academic studies in the field has considerably increased recently. Educators have also attached importance to classroom implementations to raise their learners’ autonomy over time. In this classroom action research study at a university in Turkey, I aimed to present the findings to this question: What is my learners’ level of awareness regarding their own learning and study habits? This article will present the results of this classroom inquiry based on a portfolio task that asked learners to prepare an oral report about their study habits. Data were collected through student notes, my notes on the whiteboard, and observations throughout the task. The thematic analysis method was used to analyze patterns in the data. The results suggest that learners are good at accessing study materials according to their identified needs. Although they have some effective strategies for how to learn, these strategies are outnumbered by source selection strategies in the students’ suggestions list. This article may be useful to those who are interested in promoting learner autonomy through classroom activities.